Pemanfaatan WebGIS untuk Pemetaan Wilayah Rawan Longsor Kabupaten Boyolali dengan Metode Skoring dan Pembobotan - Muhammad Sholikhan; Sri Yulianto Joko Prasetyo; Kristoko Dwi Hartomo (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
WebGIS is an online-based application of Geographic Information System, this application is a combination of web design and web mapping. WebGIS is mainly used for publishing map-based spatial information. Therefore, the author utilized webGIS, in order to mapping area that prone to landslides by using scoring and weighting methods. Parameters that used in this paper referring to the estimation model by Puslittanak in 2004, the parameters were rainfall, rock type, slope, land use, and type of soil maps. The determination of area prone to landslides was carried out by multiplying score by weight for each parameter, subsequently, the result was added up according to the reference of Puslittanak. The result of this study indicates that there are 4 sub-districts with high disaster-prone level, the sub-districts are Ampel, Cepogo, Musuk, and Selo. The final result of the map processed into a webGIS by applying Google maps service and framework bootstrap; the webGIS can be accessed by internet browser.